2006
DOI: 10.1111/j.1365-2214.2006.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor, visual and egocentric transformations in children with Developmental Coordination Disorder

Abstract: The inability of the DCD group to utilize specific motor imagery instructions and to perform egocentric transformations lends some support to the IMD hypothesis. Future work needs to address the question of whether the IMD itself is subgroup-specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
82
2
5

Year Published

2009
2009
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 39 publications
(95 reference statements)
3
82
2
5
Order By: Relevance
“…combining responses to 45 and 315 ) to allow sufficient responses at each angle for analysis. This is a common technique when analysing such data (Harris, et al, 2000;Roelofs, et al, 2002;Williams, Thomas, Maruff, Butson, & Wilson, 2006). However, this technique could be criticised given our findings that responses to left and right hands differed when presented in CW compared to CCW directions.…”
Section: Discussionmentioning
confidence: 99%
“…combining responses to 45 and 315 ) to allow sufficient responses at each angle for analysis. This is a common technique when analysing such data (Harris, et al, 2000;Roelofs, et al, 2002;Williams, Thomas, Maruff, Butson, & Wilson, 2006). However, this technique could be criticised given our findings that responses to left and right hands differed when presented in CW compared to CCW directions.…”
Section: Discussionmentioning
confidence: 99%
“…Caeyenberghs, van Roon, Swinnen, & Smits-Engelsman, 2009;Deconinck et al, 2009), this is not the case for children with DCD. The speed-accuracy trade-offs observed in the actual movements of children with DCD are not present when they imagine performing those same movements (Maruff et al, 1999;Wilson et al, 2001), and they are less accurate than their peers when performing imagined hand and whole-body rotations (Williams et al, 2006;Williams et al, 2008). This apparent MI deficit indicates that children with DCD have difficulty simulating movements internally which likely hampers their ability to predict the outcome of a selected movement plan, with movement planning and internal modelling ability thereby reduced.…”
mentioning
confidence: 87%
“…Such transformations allow individuals to take on the perspective of other people (Zacks, Mires, Tversky, & Hazeltine, 2002), an important component of motor learning through modelling. Our previous studies have demonstrated that the complexity of this task also means we are less likely to find ceiling effects in terms of accuracy, providing more detailed information regarding possible MI deficits (Williams et al, 2006;Williams et al, 2008). We expected the hemiplegia and DCD groups to show similar performance deficits in MI tasks, when compared to a typically developing comparison group.…”
mentioning
confidence: 95%
See 2 more Smart Citations